Pendekatan Saintifik Dalam Pembelajaran Tematik PadaKelas Rendah Sd Muhammadiyah 24 Gajahan SurakartaTahun 2016/2017 - Iswandari, Watik, Drs. Muhroji, S.E., M.Pd., M.Si (2017)
This study aimed to describe the scientific approach in thematic learning in low grade 24-Gajahan SD Muhammadiyah Surakarta in 2016/2017. Qualitative descriptive research with case study research design. The data collection technique used interview, observation and documentation. Test the validity of the data with source triangulation. Data analysis included data reduction, data presentation, and conclusion. Based on the results of this study concluded that 1) the learning plan made by the teacher, but the writing KD, indicators, and there is still learning objectives that need to be addressed. Teacher makes learning steps using a scientific approach to the assessment of attitudes, knowledge and skills. 2) Implementation of thematic learning by emphasizing the scientific approach but not fully in accordance with the RPP made, teachers are still difficulties in carrying out activities to try and ask. 3) teachers to assess attitudes, knowledge and skills of students, but in the assessment of the assignment and oral test are not using the guidelines pensekoran. 4) obstacles encountered by teachers, there is no match between the syllabus to guide a teacher either in writing KD, Indicators and learning objectives, time constraints in activities to try, reasoning, enter a value with jumalah KD that many, in the assessment of the attitude of the teachers have not been using the self-assessment and between friends. 5) the efforts of teachers, adjusting the existing systematics, forming groups, giving inducement questions and do not procrastinate in making judgments